The Contribution of Social Conflict with Peers toward Self-Confidence - Indah Octaviyana; Firman Firman; Daharnis Daharnis (International Journal of Research in Counseling and Education, 2017)
Some students still have less self-confidence. Students’ self-confidence is thought to be related to social conflict with peers. The study aims to describe the contribution of social conflict with peers toward self-confidence. This research used quantitative approach with descriptive-correlational method. The population of this research are high school students Pringsewu Lampung, with sample 280 students using propotional stratified random sampling. Data collection using questionnaire with Likertscale model, with instrument reliable: social conflict with peers 0.843 and students' self-confidence 0.878. Data were analyzed using simple regression. The results of the research shows that the social conflict with peers contributed (7.7%) toward students' self-confidence.